Sintesis Kristalin Selulosa Berbahan Limbah Pelepah Pisang - Rahmawati, Ayu; Faidah, Lutfatin; Ramadhan Yogaswara, Rachmad (Jurnal Fisika Unand, 2025)
Nanocrystalline cellulose (CNC) was successfully synthesized from banana sheath waste and demonstrated promising potential for applications in biocomposites, sustainable materials, and biomedical fields. This study aimed to produce CNC through an environmentally friendly chemical process while investigating the effects of bleaching temperature and acid concentration on CNC yield and properties, in accordance with ISO/TS 20477:2017. The process involved delignification using 17% NaOH at 100°C for 1.5 hours to remove lignin, followed by bleaching with 10% H₂O₂ for 1.5 hours at various temperatures (70°C–90°C) to enhance cellulose purity. Acid hydrolysis using H₂SO₄ at concentrations of 10%–30% was conducted at 45°C for 40 minutes to break down amorphous regions and form nanocrystalline structures. Chesson-Datta analysis revealed cellulose, hemicellulose, and lignin contents of 80.32%, 5.257%, and 3.26%, respectively. Optimal conditions were found at 80°C bleaching temperature and 10% acid concentration, yielding 2.5606 g of CNC. SEM-EDX analysis showed smooth fibrous morphology with 63.55% carbon and 35.83% oxygen content, while XRD analysis indicated particle sizes ranging from 8.76 to 24.12 nm, with an average of 14.25 nm.